Tetrakis(N-heterocyclic carbene)-diboron(0): double single-electron-transfer reactivity - Fan, Jun (2023)
The use of 1,3,4,5-tetramethylimidazol-2-ylidene (IMe) to coordinate with diatomic B2 species afforded a tetrakis(N-heterocyclic carbene)-diboron(0) [(IMe)2B-B(IMe)2] (2). The singly bonded B2 moiety therein possesses a valence electronic configuration 1σg21πu21πg*2 with four vacant molecular orbitals (1σu*, 2σg, 1πu', 1πg'*) coordinated with IMe. Its unprecedented electronic structure is analogous to the energetically unfavorable planar hydrazine with a D2h symmetry. The two highly reactive πg* antibonding electrons enable double single-electron-transfer (SET) reactivity in small-molecule activation. Compound 2 underwent a double SET reduction with CO2 to form two carbon dioxide radical anions CO2•-, which then reduced pyridine to yield a carboxylated pyridine reductive coupling dianion [O2CNC5(H)5-C5(H)5NCO2]2- and converted compound 2 to the tetrakis(N-heterocyclic carbene)-diborene dication [(IMe)2B═B(IMe)2]2+ (32+). This is a remarkable transition-metal-free SET reduction of CO2 without ultraviolet/visible (UV/vis) light conditions.